Study on optimized principles of process parameters for environmentally friendly machining austenitic stainless steel with high efficiency and little energy consumption. Issue 1 (July 2015) - Zhang, Yawei; Zou, Pan; Li, Beizhi; Liang, Steven
Abstract Green manufacturing is one of the important development directions for advanced manufacturing technology. In this paper, the orthogonal turning experiment of multiple factors with the minimal quantity lubrication (MQL), dry machining, and wet machining is designed to contrast the machinability for austenitic stainless steel in order to realize environmentally friendly machining with high efficiency, excellent surface quality, energy conservation, and little consumption for austenitic stainless steel. On the basis of the experiment results, in which the conditions of MQL or dry machining instead of wet machining are given, the optimized principle of process parameters for high surface quality and environmentally friendly machining austenitic stainless steel with high machining efficiency and little energy consumption is found and proposed by the comprehensive evaluation of the integrated mechanism of the process parameters with relative cutting-specific energy, unit cutting force, surface roughness, and process condition of MQL and dry machining. The research conclusions have theoretical and practical importance for production and process to give the relevant optimized principle of process parameters for machined hardening stainless steels by studying the integrated mechanism of the process parameters especially on the basis of the orthogonal experiment of multiple factors with little experiment consumption and cost.